HIF-1α and rapamycin act as gerosuppressant in multiple myeloma cells upon genotoxic stress. Issue 16 (17th August 2016) - Coudre, Clémence; Alani, Julien; Ritchie, William; Marsaud, Véronique; Sola, Brigitte; Cahu, Julie
ABSTRACT: Multiple myeloma (MM) is still an incurable hematological malignancy. Despite recent progress due to new anti-myeloma agents, the pathology is characterized by a high frequency of de novo or acquired resistance. Delineating the mechanisms of MM resistance is essential for therapeutic advances. We previously showed that long-term genotoxic stress induces the establishment of a senescence-associated secretory phenotype, a pro-inflammatory response that favors the emergence of cells with cancer stem-like properties. Here, we studied the short-term response of MM cells following treatment with various DNA damaging agents such as the energetic C-ion irradiation. MM cells are highly resistant to all treatments and do not enter apoptosis after they arrest cycling at the G2 phase. Although the DNA damage response pathway was activated, DNA breaks remained chronically in damaged MM cells. We found, using a transcriptomic approach that RAD50, a major DNA repair gene was downregulated early after genotoxic stress. In two gerosuppression situations: induction of hypoxia and inhibition of the mammalian target of rapamycin (mTOR) pathway, we observed, after the treatment with a DNA damaging agent, a normalization of RAD50 expression concomitant with the absence of cell cycle arrest. We propose that combining inhibitors of mTOR with genotoxic agents could avoid MM cells to senesce and secrete pro-inflammatory factors responsible for cancer stem-like cell emergence and, in turn, relapse of MM patients.